Gamification in a Flipped Classroom Using Articulate Storyline for Junior High School Students’ Vocabulary Mastery - Agustin Putri Intan Permata; Yudhi Arifani; Slamet Asari (JEELS (Journal of English Education and Linguistics Studies), 2025)
This study aims to design gamification-based- instructions using articulate storyline in a flipped classroom setting to improve vocabulary mastery of junior high school students and to examine how students’ perspective on this approach compared to traditional methods. The study employs a Research and Development (R&D) methodology, guided by the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The results show that there is a significant improvement in students’ vocabulary mastery, with an average gain of 30%, and over 85% of students found the gamified activities significantly more engaging and motivating. The study concludes that using the Articulate Storyline in conjunction with gamification in a flipped classroom environment significantly improves both student engagement and vocabulary mastery. These findings provide not only insightful information that positions gamified learning as a strong substitute for conventional pedagogy but also further advancements in instructional design.